The dead body: myths, rites and superstitions - Martins, Moisés de Lemos (2013)
This study is of a predominantly socio-anthropological nature, dealing with the traditions, beliefs, myths, rites and finally, how the human community imagines the post mortem and treats someone who has died. Thus, following a brief historical digression about death in the West, based on the works of Philippe Ariès (1975 and 1977), Louis-Vincent Thomas (1985), and Maria Manuel Oliveira (2007), my purpose is to focus primarily on contemporary practice, where the transformations wrought by technology on culture and the media throughout the twentieth century, have changed our sense of both life and death.